(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Mushroom cultivation presents a promising avenue for sustainable food production and economic diversification, leveraging readily available agricultural and forestry byproducts as growth substrates. Diverse edible mushroom species, including Shiitake (Lentinula edodes), Oyster (Pleurotus spp.), King Oyster (Pleurotus eryngii), and Button (Agaricus bisporus), exhibit specific substrate preferences, influencing their nutritional and therapeutic properties. While global interest in mushroom farming is expanding, Namibia faces challenges such as climate and suitable strain availability. This review explores the potential of utilizing locally abundant resources as alternative substrates, focusing on Acacia bush sawdust, shredded Prosopis branches, Kalahari melon residues, millet straw, sorghum stalks, and groundnut shells. By comparing successful case studies from other regions, we aim to investigate the impact of these substrates on the growth, nutrition, and potential therapeutic properties of the selected edible mushroom species. This study aims to demonstrate the feasibility of adapting mushroom production to local resources and conditions in Namibia, promoting sustainable agriculture, rangeland restoration, and the creation of local economic opportunities.